Characterisation of humic acids in boreal mires depending on a peat type - Krumins, J.; Klavins, M. (Boreal Environment Research Publishing Board, 2024)
The main question addressed in this study was the ongoing discussion about the humification of organic matter in different environments. We aimed at demonstrating the relation between organic matter transformation in boreal fens and raised bogs and related humic acid properties, depending on the precursor biota and environmental conditions. To highlight the differences between humic acids in different peat types, the main methods applied were based on the elemental and spectroscopic analysis and the comparison of the data obtained. The main findings pointed to differences in the concentration of aromatic compounds in humic acids, depending on peat type, i.e., the aromaticity of humic acids in fen peat was comparatively higher than that of humic acids in raised bog peat, which appeared to be related to fen peat formation from lignin-rich higher vegetation that provided aromatic macromolecules. While raised bog peat-forming bryophytes did contain molecules rich in phenols, the aliphatic compounds prevailed in the composition of humic acids. We found that fen peat humic acids were also more affected by carbohydrate degradation over time, leading to apparent functional differences between boreal fen and raised bog peat humic acids. The humification process itself seems to be initialized similarly in boreal fens and raised bogs, while comparatively higher aromaticity of fen peat humic acids appears to be related to high lignin content, which joins the humification process at a later stage of peat formation due to slow decomposition rate and thus it per se does not indicate a humification processes being different from raised bog peat. Albeit lignin involvement changes the microbial pathways to degrade the organic material in fens at a later stage, and in raised bogs due to uniform lower vegetation cover, the microbial pathways do not change significantly over time.